Production and Circulation of Vernacular Italian Books Related to the Jesuit Mission in Japan in the Sixteenth Century - Favi, Sonia (Annali di Ca’ Foscari: Serie Orientale, 2018)
The reports and histories compiled by the members of the Society of Jesus in the second half of the sixteenth century were among the earliest European sources to treat ‘Japan’ as a geographical and political reality. The peculiarity of the Jesuit approach, focused on research and adaptation, is reflected in the variety of their contents, encompassing descriptions of geography, politics, society, language, religion and art. The reports were also the earliest sources on Japan to reach a wider public in Europe. They were not only delivered to Coimbra, Rome and to the different Jesuit houses, but also distributed commercially, in the form of letter-books,  throughout Europe. It can be presumed that the impact of the letter-books on European readership was enhanced by the growing popularity of periodical publications and by the expansion of the publishing market. This paper will use the reports published in vernacular Italian as a case study, and investigate the nature of such readership and how the reports fit into the Italian book market of the sixteenth century. It will analyse them in light of the cultural and economical processes that led to their production and circulation, focusing on publishing houses, editions and formats, in order to evaluate the editorial policies that led to their circulation.